Clinico demographic profile and short-term outcome of Pediatric Idiopathic Intracranial Hypertension in a tertiary care hospital of Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Diagnosis of IIH (idiopathic intracranial hypertension) in children is challenging. The pathogenesis of IIH is still largely unknown. The aim of this study to evaluate the clinico-demographic profile and short-term outcome of IIH among Bangladeshi children.Methodology: This observational cohort study was done in pediatric Neurology Department, National Institute of Neurosciences and Hospital Bangladesh from January 2018 to July 2019. Total 19 cases were enrolled who were clinically suspected and/or had normal CSF with opening pressure (OP) above 250 mmH2O. They were further categorized as “definite IIH”, definite IIH without papilledema, and “probable IIH”. Clinical, radiological profile and short-term outcome were analyzed by SPSS version 22.Result: Among them most were probable IIH (74%). Episodic (57.9%), moderate, diffuse headache was the predominant symptom along with vomiting, double vision, unilateral VI nerve palsy and papilledema. Obesity was found in 21% cases. Mean CSF pressure was 21.84+7.62cm H2O and found high in definite IIH. All the cases were treated with acetazolamide and serial LP was done in 4(15.8%) cases. Definite IIH requires longer hospital stay (6.42 ± 2.87days). Recurrence was observed in 10.5% cases and visual impairment was found in 15.8% cases.Conclusion: This study found wide range of diversity between clinical feature and CSF opening pressure in Pediatric IIH and diagnostic confirmation was challenging. Initial treatment response was satisfactory with a low recurrence rate.J Bangladesh Coll Phys Surg 2024; 42: 161-168